MEASUREMENT OF SUCCESS FACTORS OF PORT INFORMATION SYSTEMS (Third Sector Social Economic Review, 2018)
The contributions of information systems to the development of international trade movements are a recently discussed phenomenon. The existence and effective use of information systems is indispensable for the success of port operations which are at the center of international business activities. Increasing competition among ports forces managers to maximize efficiency and efficiency. The effectiveness of information systems enable to solve the problems allied with increases in the amount of freight observed in ports, ship dimensions, changing customer demands and etc. and to facilitate implementations for ensuring sustainable harbor efficiency. In this research, it is aimed to analyze the success of the information systems used by our ports with different factors and to make an up-to-date and  useful contribution. In this direction, a survey was based on the ports belonging to TURKLIM (Port Operators Association of Turkey). Measurement of success factors of information systems are based on the updated model of De Lone and Mc Lean and used 6 variables as ""Information Quality"", ""System Quality"", ""Service Quality"", ""Usage"", ""User Satisfaction"" and 'Net Benefit''. The findings of the research show that system quality and service quality are critical factors in the success of the information systems used in our ports. The quality of the information, the quality of the system and the service quality reveal user satisfaction, and the increased user satisfaction has a positive effect on the success of the system and the net benefits obtained.
Keywords: Port Information Systems; Information Systems Success Model; Information Quality; System Quality; Service Quality; Net Benefits